2019
DOI: 10.1177/0963693519879696
|View full text |Cite
|
Sign up to set email alerts
|

Salt template zirconia reinforcing particles as possible reinforcement for PMMA matrix composite

Abstract: To obtain flakes like zirconia particles at relatively low temperature, the synthesis method for producing zirconia particles on the surface of salt particles that serve as a template is examined. The produced particles are incorporated as reinforcement in the poly(methyl methacrylate) matrix to obtain a composite material. The particles were characterized by the X-ray diffraction, Fourier-transform infrared spectroscopy, and image analysis. The morphology of the particles and composites was examined using a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The indent was in the shape of a pyramid sheath resembling a square, and the diagonal length was then measured. The micro-hardness of the samples was also measured, using Vickers micro-hardness tester DURIMET I Kleinharteprufer (Leitz, Wetzlar, Germany) with a load of 4.9 N according to ASTM E384-16 [ 33 ]. Three indentations were performed, obtaining six diagonal lengths for the calculation of hardness.…”
Section: Methodsmentioning
confidence: 99%
“…The indent was in the shape of a pyramid sheath resembling a square, and the diagonal length was then measured. The micro-hardness of the samples was also measured, using Vickers micro-hardness tester DURIMET I Kleinharteprufer (Leitz, Wetzlar, Germany) with a load of 4.9 N according to ASTM E384-16 [ 33 ]. Three indentations were performed, obtaining six diagonal lengths for the calculation of hardness.…”
Section: Methodsmentioning
confidence: 99%
“…Elmadani et. al, [53], reported the greatest increase in hardness values with a 5wt.% loading of ZrO , resulting in a 59% increase in hardness. When ller particles, such as MWCNTs, are added to a PMMA matrix, they can interact with the polymer chains and act as reinforcement, improving the mechanical properties of the resulting composite material, including its hardness.…”
Section: Tensile Propertiesmentioning
confidence: 96%
“…The study by Elmadani et. al, [53], investigated the effect of adding ZrO or TiO particles to a PMMA matrix on the hardness of the resulting composite materials. The study reported an increase in hardness values with the addition of these particles.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…All the stretching vibrations observed in the PMMA appeared in the complex/PMMA LSCs with higher intensity. The van der Waals interactions between PMMA and the metal complex are very weak, and the amount of complex used does not affect the transparency of the LSCs [29][30][31].…”
Section: Characterization Of Complex/pmma Lscsmentioning
confidence: 99%